Coal fly ash activated by NaOH roasting: Rare earth elements recovery and harmful trace elements migration. (15th September 2022) - Wu, Guoqiang; Wang, Tao; Chen, Gan; Shen, Zhoujie; Pan, Wei-Ping
Graphical abstract: Highlights: Coal fly ash by NaOH roasting enhances the volatilization of mercury at lower temperatures. More water-soluble arsenic and selenium compounds are generated by NaOH roasting. More acid-soluble lead and cadmium compounds are obtained by NaOH roasting. NaOH roasting can effectively improve the recovery of rare earth elements in coal fly ash. Abstract: Coal fly ash (CFA) has been considered an important alternative resource for rare earth elements (REEs) and other critical metals such as Ge, Ga, U, etc. Concerns regarding the migration and transformation of harmful trace elements (HTEs: Hg, As, Se, Pb, Cd, Cr) from CFA to the environment are of great significance for the technical design of the recovery of REEs from CFA as well as its economic evaluation and environmental impact assessment. Here, the migration and transformation of these HTEs during the recovery of REEs from CFA activated by NaOH roasting were investigated. The recovery of REEs from CFA was above 90% under the conditions of the alkali-to-ash ratio of 1.2 and roasting temperature of 318 °C. In the NaOH roasting process, mercury compounds, i.e., Hg2 Cl2, HgCl2, and HgSO4, were converted into HgO, which was then partially reduced to elemental Hg (Hg 0 ) in the water generated during the roasting process and promoted the release of Hg from CFA. In addition, other HTEs, e.g., As, Se, Pb, Cd, and Cr, were also transformed into compounds during the NaOH roasting process that were easier to be leached out during the following water and acid leaching process compared to that without the roasting process. For example, As compounds (As2 O5, As2 O3, Ca3 (AsO4 )2, and FeAsO4 ) were converted into Na3 AsO4 . Se compounds (Se, SeO2, and CaSeO3 ) were converted into Na2 SeO3 . PbSO4 and PbCl2 were converted into PbO. CdCl2 and CdSO4 were converted into CdO. CrO3, CrCl3, and Cr2 (SO4 )3 were converted into Na2 CrO4 and NaCrO2 . The experimental results of this work provided insights into understanding the migration and transformation of these HTEs and the associated leaching behavior during the recovery of REEs from CFA activated using a NaOH roasting approach.